On Contextually Embedded Choices - Diego Lanzi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2004)
Starting from Amartya Sen's works on rational behaviour, in this essay a contextually-embedded choice theory is presented. Using concepts and tools from poset mathematics, we show how to inject in rational choice theory cultural and social effects. Specifically, we define some choice super-structures seen as choice sets' transformations imposed by accepted external consistency of choice requirements. As we will argue, these applications can be of some help in explaining preference changes within different contexts of choice. Hence, using the same analytical framework, some well-known results about maximizing and optimizing behaviour may be confirmed as well as some insights on intransitive choices phase out.
Keywords: 330; Präferenztheorie; Rationalität